Congratulation of Publishers of the Magazine „Slauga. Mokslas ir praktika“ - „Slauga. Mokslas ir praktika“, The Publishers of the Magazine (Slauga. Mokslas ir praktika, 2020)
Congratulation of Publishers of the Magazine „Slauga. Mokslas ir praktika“.